Differentiation of T Helper 17 Cells May Mediate the Abnormal Humoral Immunity in IgA Nephropathy and Inflammatory Bowel Disease Based on Shared Genetic Effects - Qing, Jianbo; Li, Changqun; Hu, Xueli; Song, Wenzhu; Tirichen, Hasna; Yaigoub, Hasnaa; Li, Yafeng (Frontiers in Immunology, 2022)
Background: IgA Nephropathy(IgAN) is the most frequent glomerulonephritis in inflammatory bowel disease (IBD) ,However, the inter-relational mechanisms between them are still unclear. This article aimed to explore the shared gene effects and potential immune mechanisms in IgAN and IBD. Methods: The microarray data of IgAN and IBD in the Gene Expression Omnibus (GEO) database were downloaded. The differential expression analysis was used to identify the shared differently expressed genes (SDEGs), and the shared transcription factors(TFs) and microRNAs (miRNAs) in IgAN and IBD were screened using humanTFDB, HMDD, ENCODE,JASPAR, and ChEA databases. Moreover, weighted Gene Co-Expression Network Analysis (WGCNA) was used to identify the shared Immune-related genes (SIRGs) related to IgAN and IBD, and R software package org.hs.eg.db (Version3.1.0) were used to identify common immune pathways in IgAN and IBD. Results: 64 SDEGs and 28 SIRGs were identified, and The receiver operating characteristic curve(AUC) of 64 SDEGs was calculated and two genes(MVP, PDXK) with high AUC in both IgAN and IBD were screened out as potential diagnostic biomarkers. We then screened 3 shared TFs(SRY, MEF2D and SREBF1) and 3 miRNAs(hsa-miR-146，hsa-miR-21 and hsa-miR-320), and further found that the immune pathway of 64SDEGs, 28SIRGs and 3miRNAs were mainly including B cell receptor signaling pathway, FcγR-mediated phagocytosis, IL-17 signaling pathway, toll-like receptor signaling pathway, TNF signaling pathway,TRP channels, T cell receptor signaling pathway, Th17 cell differentiation, and cytokine-cytokine receptor interaction. Conclusion: Our work revealed the differentiation of Th17 cells may mediate the abnormal humoral immunity in IgAN and IBD patients and identified novel gene candidates that could be used as biomarkers or potential therapeutic targets.